2018
DOI: 10.7150/thno.21072
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells-derived exosomes are more immunosuppressive than microparticles in inflammatory arthritis

Abstract: Objectives: Mesenchymal stem cells (MSCs) release extracellular vesicles (EVs) that display a therapeutic effect in inflammatory disease models. Although MSCs can prevent arthritis, the role of MSCs-derived EVs has never been reported in rheumatoid arthritis. This prompted us to compare the function of exosomes (Exos) and microparticles (MPs) isolated from MSCs and investigate their immunomodulatory function in arthritis.Methods: MSCs-derived Exos and MPs were isolated by differential ultracentrifugation. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
321
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 385 publications
(329 citation statements)
references
References 38 publications
7
321
0
1
Order By: Relevance
“…Intercellular communication between SCs and immune cells is achieved through their respective EVs. For example, SC-EVs internalized by immune cells inhibit the proliferation and activation of the latter (29,30) (Figure 1). SC-EVs preferentially accumulate in injury sites to inhibit the pro-inflammatory response of immune cells (31).…”
Section: Bidirectional Interaction Of Stem Cells With Immune Cells Thmentioning
confidence: 99%
See 2 more Smart Citations
“…Intercellular communication between SCs and immune cells is achieved through their respective EVs. For example, SC-EVs internalized by immune cells inhibit the proliferation and activation of the latter (29,30) (Figure 1). SC-EVs preferentially accumulate in injury sites to inhibit the pro-inflammatory response of immune cells (31).…”
Section: Bidirectional Interaction Of Stem Cells With Immune Cells Thmentioning
confidence: 99%
“…On the one hand, SC-EVs have been reported to induce the immune response of T helper type 1 (Th1) conversion to T helper type 2 (Th2). For example, SC-EVs drove the shift from Th1 toward Th2 cells and reestablished Th1/Th2 homeostasis by downregulating pro-inflammatory TNF-α and INF-γ and upregulating anti-inflammatory IL-10 or IL-4 (29,44,51,74,76) ( Table 1). Moreover, SC-EVs could also regulate Th2 immune response toward Th1.…”
Section: Stem Cell-derived Extracellular Vesicle Potentials In T Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic effect of MSC‐derived exosomes on arthritis have also been investigated. In several studies, intravenous or intra‐articular exosomes isolated from MSCs were shown to inhibit macrophage activation, inflammation, and cartilage destruction in in vitro and in vivo models via inhibition of catabolisis, inflammatory markers and apoptosis, increase of collagen type II synthesis, and modulation of T and B cells …”
Section: Role Of Exosomesmentioning
confidence: 99%
“…Induction of IL-10 Suppression of IL-1β, IL-6, IL-7, iNOS, and TNF-α expression [64] Cancer Mediation Proinflammatory Breast cancer Macrophage Activation of NF-κB Production of IL-6, TNF-α, G-CSF, and CCL2 [66] Mediation Ovarian cancer Monocyte Activation of NF-κB and STAT3 Production of IL-1β, IL-23a, IL-6, TNF-α, and CCL5 [68] Mediation Immunomodulation/ escape Nasopharyngeal cancer T cell Promote Treg cell induction Enhance Treg chemoattarction Inhibition of T cell proliferation, Th1 and Th17 differentiation and promote Treg induction [70,73] Mediation Cervical cancer NK cell Inhibition of NK cell cytotoxicity [71] Diabetics Therapeutic Anti-inflammatory Mesenchymal stem cells Bone marrowderived dendritic cell Decreased BDMC infiltration [79] Arthritis Mediation Pro-inflammatory Synovial fibroblast Articular chondrocytes Upregulation of MMP-3, MMP-13, IL-1β, IL-6, and VEGF [80] Mediation Pro-inflammatory Synovial fibroblast Cartilage Increased proteoglycan loss [40] Mediation Pro-inflammatory Synovial fibroblast Synovial fibroblast Activation of NF-κB and induce MMP-1 expression [81] Therapeutic Anti-inflammatory Dendritic cells -Suppress swelling of joints Suppress the onset of disease Reduce the severity of arithritis [82] Therapeutic Anti-inflammatory Mesenchymal stem cells T cell Inhibit T lymphocyte proliferation and decrease CD4 + and CD8 + T cell subsets Increased Treg cells [83] B cell Inhibit plasmablast proliferation and suppress total IgG production [83] Therapeutic Anti-inflammatory Mesenchymal stem cells Macrophage Inhibit activation of macrophage Suppression of TNF-α, induction of IL-10 production [84] Neurological disorders Onset Disease progression Microglia Brain cells Accumulation of Tau protein [89] Therapeutic Therapeutic Mesenchymal stem cells…”
Section: Colon Tissuementioning
confidence: 99%